The Predictive Value of Sleep Disturbance, REM Latency, and Chronotype on the Onset of Major Depressive Episodes: A Systematic Review - Anisa Faradiba Ratrin; Andy Soemara (International Medical Journal Corp. Ltd, 2025)
Background. Major Depressive Disorder (MDD) is a leading cause of global disability, creating an urgent need for effective prevention strategies. The clinical paradigm is shifting from viewing sleep disturbance as a mere symptom of depression to recognizing it as a prodromal risk factor. This systematic review aims to synthesize and critically evaluate prospective, longitudinal evidence on the association of general sleep disturbance (primarily insomnia), the objective polysomnographic marker of Rapid Eye Movement (REM) latency, and the circadian trait of chronotype with the first-onset of a major depressive episode in initially non-depressed populations. Methods. A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library databases was conducted from inception to the present, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligibility criteria, structured by the Population, Intervention/Comparator, Outcome (PICO) framework, included prospective cohort studies assessing baseline sleep parameters in populations free of depression at enrolment. The primary outcome was incident MDD. The methodological quality of included studies was assessed using the Newcastle-Ottawa Scale (NOS). Results. Twenty-one prospective cohort studies, encompassing over 250,000 participants, met the inclusion criteria. The evidence consistently demonstrates a strong, dose-dependent association between baseline insomnia and the subsequent onset of depression, with risk ratios often exceeding 2.0. Objective polysomnographic data reveal that shortened REM latency is a significant predictor of incident depression, particularly in cohorts with a high familial risk for affective disorders, suggesting it serves as a potent vulnerability marker. Furthermore, a robust body of evidence from large-scale cohort studies identifies an evening chronotype as an independent risk factor for incident depression, even after controlling for sleep duration and other potential confounders. Discussion. The convergence of evidence from subjective reports, objective neurophysiology, and circadian assessments points toward a multi-faceted dysregulation of sleep-wake systems as a core etiological pathway in the development of MDD. The findings are interpreted through integrated neurobiological frameworks, including the hyperarousal-HPA axis hypothesis, the emotional dysregulation hypothesis centered on REM sleep's role in affective homeostasis, and the circadian misalignment hypothesis. These mechanisms suggest that sleep disturbance is not an epiphenomenon but a potentially causal factor that precedes and precipitates the clinical manifestation of depression. Conclusion. General sleep disturbance, shortened REM latency, and an evening chronotype are significant and reliable antecedent risk factors for the onset of major depressive episodes. These findings have profound clinical implications, advocating for the integration of sleep and circadian assessments into standard mental health screening and positioning interventions such as Cognitive Behavioral Therapy for Insomnia (CBT-I) and chronotherapy as viable primary prevention strategies for depression.